FORMULASI SIRUP EKSTRAK ETANOL DAUN PARE (Momordica charantia L.) DENGAN GELATIN SEBAGAI PENGENTAL DAN AKTIVITAS MUKOLITIKNYA - Ririn Lispita Wulandari; Eli Mahmud; Mufrod Mufrod (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2018)
ABSTRACTEthanol extract of bitter melon leaves at a concentration of 5% has been shown to have mucolytic activity. For ease of use that is made of dosage forms syrup. Thickening agent serves to increase the viscosity and resist settling process resulting in a stable syrup. Gelatin has the ability to improve settling extract better than other thickening. This study aims to determine the effect of variations in the concentration of gelatin to the physical-chemical properties and activity of ethanol extract syrup mukolitik pare leaves the cow intestine mucus in vitro. Extraction of leaf bitter melon is done by percolation. EEDP was made into three syrup formulas using 1% (FII), 2% (FIII), 3% (FIV) gelatin thickener. There is also syrup without extract and gelatin (FI) as a control. The four syrup formulas were examined for physical chemical properties (organoleptic, homogeneity, pH, viscosity), and tested their mucolytic activity. Data on the results of activity tests in the form of viscosity were analyzed by Kruskal-Wallis followed by Mann-Whitney. Data from organoleptic examination, homogeneity, Ph were analyzed descriptively, while viscosity with Linear Regression. The results showed that EEDP syrup with a gelatin concentration of 1%; 2%; 3% have mucolytic activity. The results of examination of the physico-chemical properties of FII, III, and IV syrups have the same taste and color, sweet and bitter, and are greenish black in color, while FI syrup is sweet and yellowish in color. Homogeneous FI syrup, FIII and FIV syrup are evenly distributed, while FII syrup has coarse particles. Fourth pH normal syrup formula. Increased concentration of gelatin (1%; 2%; 3%) can increase the viscosity of syrupKeywords: ethanol extract of bitter melon leaves, syrup, gelatin